2012
DOI: 10.5120/5605-7864
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects on Unsteady Free Convection Flow Past a Vertical Plate with Newtonian Heating

Abstract: The unsteady free convection flow with thermal radiation past a vertical plate with Newtonian heating has been studied. The governing equations have been solved numerically by the implicit finite difference method of Crank-Nicolson's type. The variations of the fluid velocity and temperature are presented graphically. It is found that the fluid velocity decreases near the plate and it increases away from the plate with an increase in either Prandtl number or radiation parameter. It is also found that the fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…An increase in inverse permeability parameter (K) generates a substantial increase in heat transfer rates, whereas increasing first order momentum slip parameter has the opposite effect. Heat transfer rates are also found to be enhanced with increasing Prandtl number and radiation-conduction parameter, R. Similar results have been obtained for Newtonian flows by Das and colleagues [36] and for nanofluid flows by Hady and colleagues [37]. Figure 7 shows the influence of velocity ratio, inverse permeability parameter and first order momentum slip parameter on the dimensionless mass transfer rates at the sheet surface.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…An increase in inverse permeability parameter (K) generates a substantial increase in heat transfer rates, whereas increasing first order momentum slip parameter has the opposite effect. Heat transfer rates are also found to be enhanced with increasing Prandtl number and radiation-conduction parameter, R. Similar results have been obtained for Newtonian flows by Das and colleagues [36] and for nanofluid flows by Hady and colleagues [37]. Figure 7 shows the influence of velocity ratio, inverse permeability parameter and first order momentum slip parameter on the dimensionless mass transfer rates at the sheet surface.…”
Section: Resultssupporting
confidence: 79%
“…They showed that thermal radiation serves to increase thermal boundary layer thickness and modifies the velocity boundary layer characteristics. Further studies, employing the Rosseland model, have been communicated by Narahari and Ishak [32] with Newtonian heating wall conditions, Prasad and colleagues [33] for transient flow from a conical body with mass transfer, Anwar Bég and colleagues [34] for inclined plate pressure-driven unsteady radiative-convection flows, Prasad and colleagues [35] for hydromagnetic radiative convection boundary layers in porous media and by Das and colleagues [36] for transient convection-radiation with Newtonian heating. Recently, Hady and colleagues [37] have investigated thermal radiation flux effects on nanofluid transport from a stretching surface with the Rosseland flux model and viscous dissipation effects.…”
Section: Introductionmentioning
confidence: 99%
“…Raptis (1986) established the physical properties of the fluid flow implementing magnetic field. Das et al (2012) analyzed rays effects on fluid flow under the existence of Newtonian heating. Narahari and Nayan (2011) investigated the properties of free convection flow with heating radiation and species dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, numerical solutions using Runge-Kutta-Fehlberg with fourth-fifth order technique for the steady boundary-layer heat transfer flow of micropolar fluid with Newtonian heating past a stretching surface are recently obtained by Qasim et al [26]. The literature survey shows that most of the Newtonian heating problems are limited to the Newtonian fluid and mostly, they are solved using any numerical or approximate technique, see for example [27][28][29][30][31]. In fact, the Newtonian heating problems even for viscous fluid when someone is interested to get the exact solutions are much complicated and limited to few problems only.…”
Section: Introductionmentioning
confidence: 99%